Importance of intellectual capital across borders - Aw, Jia Hui (2008)
The market is now valuing changes in intellectual capital as the most significant driver affecting volatility of market values across most industries and countries. Traditional drivers of success such as tangible fixed assets and earnings are losing their popularity and influence in stock markets today.